2022
DOI: 10.1007/s00420-021-01820-w
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with symptoms of poor mental health among women factory workers in China’s supply chain

Abstract: Objective Foreign direct investment (FDI) to China has motivated increased labor migration to export processing zones (EPZs). Work environments with high occupational stress, such as production line jobs typical in EPZs, have been associated with adverse mental health symptoms. Methods A cross-sectional survey that examined occupational stress and symptoms of poor mental health was implemented among Chinese women factory workers in three electronic factories in the Tian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 81 publications
(74 reference statements)
0
9
0
Order By: Relevance
“…Thirdly, we constrained our emphasis to the frontline routine operators. Sznajder et al (2022) demonstrated that work conditions characterized by high occupational stress, low decision latitude, routine high job demands, low social support, and the combination of high effort and low rewards are associated with poor mental health symptoms. Based on this, this study emphasizes frontline routine workers who are responsible for manufacturing, filling, stacking, packing and supervising toilet S&D powder at ASD work-centers.…”
Section: Research Methodology 31 Research Limitationsmentioning
confidence: 99%
“…Thirdly, we constrained our emphasis to the frontline routine operators. Sznajder et al (2022) demonstrated that work conditions characterized by high occupational stress, low decision latitude, routine high job demands, low social support, and the combination of high effort and low rewards are associated with poor mental health symptoms. Based on this, this study emphasizes frontline routine workers who are responsible for manufacturing, filling, stacking, packing and supervising toilet S&D powder at ASD work-centers.…”
Section: Research Methodology 31 Research Limitationsmentioning
confidence: 99%
“…Job insecurity was very common, regardless of the type of precarious contract (32,38,89,90,93,98). Nine quantitative studies (25, 33, 57, 66-68, 74, 75, 80) reported job insecurity, and five of them provided the prevalence of job insecurity (25,57,67,74,75). Seven studies reported an association between job insecurity and mental health problems (33, 57, 66-68, 75, 80).…”
Section: Precarious Employment and Its Association With Mental Healthmentioning
confidence: 99%
“…These health issues are related to increased absenteeism and presenteeism, as well as decreased motivation, contentment, and commitment. These can produce increases in employee turnover and a desire to resign, resulting in low business productivity and increased medical, healthcare, and social welfare expenditures ( Asplund et al, 2022 ; Mohamed et al, 2022 ; Sznajder et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Constant work stress and pressure result in both physical and mental exhaustion, a lack of work-life balance, and decreased employee productivity ( Bhui et al, 2016 ; Bolliger et al, 2022 ; Kim and Jung, 2022 ). Hopelessness, not feeling useful, and feeling depressed in the work environment are considered factors associated with symptoms of work-related stress among factory workers ( Sznajder et al, 2022 ), highlighting the need for interventions to alleviate poor mental health symptoms among workers in high-pressure occupational environments.…”
Section: Introductionmentioning
confidence: 99%